Survey of the perception and presence of bias in the Italian judicial system (Rivista di Psicopatologia Forense, Medicina Legale, Criminologia, 2021)
It is now evident that the Italian judicial system is full of defects and gaps. There is an urgent need to implement reforms with which to limit judicial error. One of the biggest problems is the presence of prejudice that leads to the fulfilment of unjust sentences. Through the administration of an anonymous questionnaire, an attempt was made to investigate the perception and presence of prejudice in people who carry out a profession within the judiciary. A further objective is the creation of a personological profile of the typical magistrate. The main intent is to raise awareness and make professionals aware of the problems present throughout the judicial system and to be able to provide a pulse to implement changes and renovations aimed to creating a better society.